DESIGN, DEVELOPMENT, AND CHARACTERIZATION OF OCIMUM BASILICUM MUCILAGE-BASED, MODIFIED RELEASE MUCOADHESIVE GASTROSPHERES OF CARVEDILOL: OCIMUM BASILICUM MUCILAGE BASED GASTROSPHERES OF CARVEDILOL - SAKHARE SS; SAYYAD FJ (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present investigations aim to develop mucoadhesive gastrospheres of carvedilol using sodium alginate and Ocimum basilicum seed mucilage combination blend oral use. Methods: The gastrospheres were prepared by ionotropic gelation method using 32 factorial designs, the concentration of sodium alginate and O. basilicum mucilage was independent variables while % drug content (DC), % entrapment efficiency, and % drug release at 12 h were dependent variables. The gastrospheres were evaluated for other parameters such as Fourier-transform infrared (FTIR), powder X-ray diffraction, differential scanning calorimetric, and in vitro mucoadhesion studies. Results: In optimization studies from statistical second-order complete model equation among the polymers used O. basilicum mucilage had a more profound effect on DC and % encapsulation efficiency as compared to sodium alginate. The mean particle size of gastrospheres when measured by optical microscopy technique ranged from 774 to 882 μm. The percentage of gastrosphere adhering to goat intestinal mucosal tissue varied from 10% to 65% over 8 h in 0.1N HCl, whereas this was varied from 40% to 60% in phosphate buffer pH 6.8 with provided 12 h of controlled release following zero-order release pattern. Conclusion: Studies conclude that mucilage of O. basilicum can be used as controlled release mucoadhesive material in the formulation of gastrospheres.